Implementasi Algoritme AES Pada Pengiriman Data Sensor DHT11 Menggunakan Protokol Komunikasi HTTP - Aulia Rizqy Pratama; Mochammad Hannats Hanafi Ichsan; Ari Kusyanti (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
HTTP is a network protocol on the TCP / IP application layer that is used for communication or data exchange between the server and the client. There is a weakness in the HTTP protocol where the data or information transfer does not have a security or encryption process which can endanger the information or data sent on a network. There is already a development to overcome security issues on the HTTP protocol, namely by using the HTTPS protocol. However, the HTTPS protocol consumes a lot of memory and drains a lot of resources in processing so it is not recommended to be implemented in embedded systems. This study proposes to use one of the existing cryptographic algorithms implemented on the HTTPS protocol, which is the AES algorithm which plays a role in data encryption in the HTTPS protocol which fulfills the confidentiality. In this study using Arduino Uno as a microcontroller used to process DHT11 and NI Labview sensor data to display the output of the system. HTTP server and encryption process are implemented in Arduino IDE and HTTP client and decryption process at NI Labview. From the test results obtained the average value of encryption and decryption processing time is 13.048 milliseconds with the average delivery delay on the HTTP protocol by 0.091073 seconds. From the test results concluded that the AES algorithm can be implemented to secure the data transfer from the DHT11 sensor using the HTTP protocol.